The Subtitution of Kluwih Seed Flour (Artocarpus Communis) in the Noodle Production - Zania Faradiva; Tengku Mia Rahmiati; Fadlan Hidayat; Yuslinaini Yuslinaini; Cut Khairatul Mahruzi (Universitas Serambi Mekkah, 2022)
The use of kluwih seed flour in the noodle processing is an effort to diversify food and reduce consumption of wheat flour in Indonesia. This research aimed to examine the physicochemical properties of wet noodles made from kluwih seed flour. The study employed Completely Randomized Design (CRD) non factorial with the treatment of substitution ratios of wheat flour and kluwih seed flour; 10 grams: 90 grams (T1), 20 grams: 80 grams (T2), 30 grams: 70 grams (T3), and 40 grams: 60 grams (T4). The result showed that the best treatment on the composition of the wheat flour substitution with kluwih seed flour 80%: 20% (T2) with an elongation value of 30.68%, elasticity of 7.44% organoleptic test, taste 3.83 (likes), aroma 3.80 (likes) and color 3.97 (likes). Keywords: noodle, Kluwih seed flour, organoleptic, elasticity, elongation